Balancing Immune Protection and Immune Pathology by CD8+ T-Cell Responses to Influenza Infection - Duan, Susu; Thomas, Paul G. (Frontiers in Immunology, 2016)
Influenza A virus (IAV) is a significant human pathogen causing annual epidemics and periodic pandemics. CD8+ cytotoxic T lymphocyte (CTL)-mediated immunity contributes to clearance of virus-infected cells; CTL immunity targeting the conserved internal proteins of IAVs is a key protection mechanism when neutralizing antibodies are absent during heterosubtypic IAV infection. However, CTL infiltration into the airways, their cytotoxicity, and the effects of produced pro-inflammatory cytokines can cause severe lung tissue injury, thereby contributing to immunopathology. Studies have discovered complicated and exquisite stimulatory and inhibitory mechanisms that regulate CTL magnitude and effector activities during IAV infection. Here, we review the state of knowledge on the roles of IAV-specific CTLs in immune protection and immunopathology during IAV infection in animal models, highlighting the key findings of various requirements and constraints regulating the balance of immune protection and pathology involved in CTL immunity. We also discuss the evidence of cross-reactive CTL immunity as a positive correlate of cross-subtype protection during secondary IAV infection in both animal and human studies. We argue that the effects of CTL immunity on protection and immunopathology depend on multiple layers of host and viral factors, including complex host mechanisms to regulate CTL magnitude and effector activity, the pathogenic nature of the IAV, the innate response milieu, and the host historical immune context of influenza infection. Future efforts are needed to further understand these key host and viral factors, especially to differentiate those that constrain optimally effective CTL anti-viral immunity from those necessary to restrain CTL-mediated nonspecific immunopathology in the various contexts of IAV infection, in order to develop better vaccination and therapeutic strategies for modifying protective CTL immunity.